(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Career is described as an occupation for a substantial amount of a person’s life and prospects for advancement. In this context, the term profession can be extended to any kind of job as opposed to the common notion that only individuals in those professions are viewed as possessing a career. However, the term ’career’ is usually applied to careers synonymous with some types of status and professional credentials. This paper reflects study on Career Guidance and Career Decision making in Indian Context.